Tinjauan Hukum Pidana terhadap Ekspor Pasir Ilegal - Agnes Rosalia; Muhammad Fajar Hidayat (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Management of Sedimentation Results in the Sea, Sedimentation Results in the Sea are sediment in the sea in the form of natural material formed by weathering and erosion processes, which are distributed by oceanographic dynamics and deposited which can be taken for use prevent disruption of ecosystems and shipping. The use of marine sedimentation in its regulation refers to the business licensing aspect issued by the Minister by establishing planning documents, regulated in the Regulation of the Minister of Maritime Affairs and Fisheries of the Republic of Indonesia Number 33 of 2023 concerning Implementing Regulations of Government Regulation Number 26 of 2023 concerning Management of Sedimentation Results in the Sea. In managing and protecting the sea, every activity at sea pays attention to the balance and preservation of the sea, if a violation occurs, it is subject to administrative and criminal sanctions. Criminal liability for illegal sand exports refers to Article 158 of Law Number 4 of 2009 concerning Mineral and Coal Mining, beside, several primary legal materials can be used for law enforcement against sand mining, namely, the Criminal Code (KUHP), Law Number 32 of 2009 concerning Environmental Protection and Management, and the other national regulations that has same meaning of this crime.